Review of pharamacological activities and medicinal uses of Sesbania sesban - Sathiyaseelan, V.; Karunya, S.; Saruja, N. (Unit of Siddha Medicine, University of Jaffna, 2018)
Sesbania sesban which belongs to Leguminosae family is one of the most important plants in Literature of Siddha Medicine, specially used in Northern province of Sri Lanka. Because of the medicinal importance of Sesbania sesban it is used in the preparation of Medicine such as a karumsempai thailam used in Pinesam, Thalaiparam and Kapalaneerkorvai once a week. In our Medicine the leaves, flowers, roots and seeds of the plant are used in the treatment of various diseases. According to the Siddha Pharmacodynamic properties of Sesbania sesban are bitter and astringent in taste, hot in potency, pungent in post digestive stage. Based on Siddha quotation Sesbania sesban is used to treat pun, katti, karappan, kapam, theekuttam, veegkampinesam and neeratum. The pharmacological actions of Sesbania sesban such as stimulant, emmenagogue, astringent, anthelmintic, diuretic and re-solvent have been mentioned in the Siddha text-Murukaesamuthaliar. The research work was carried out for a period of 3 months from August 2017 to November 2017. The information was collected from authentic Siddha texts, research articles, scientific journals and electronic media. Seeds have stimulant, emmenagogue and astringent actions as well as roots have anthelmintic, carminative and anti-dote, leaves have anthelmintic, purgative, anti-inflammatory and demulcent,bark has stimulant, anti- inflammatory and anti-dysentric actions. The above mentioned pharmacological actions are proven scientifically. It is concluded that Sesbania sesban is widely used and highly beneficial in treatment of various disease. This study helps Siddha doctors to cure the various diseases by identifying the medical properties of Sesbania sesban
Keywords: Sesbania sesban; Pun; Katti; Karappan; Kapam; Theekuttam